Application of CT contrast medium is not associated with an increased risk for acute kidney injury in patients with decompensated cirrhosis. Issue 1 (9th November 2022) - Tergast, Tammo L.; Schulte, Benjamin; Griemsmann, Marie; Kahlhöfer, Julia; Dörge, Petra; Hinrichs, Jan B.; Kraft, Anke R. M.; Schmidt, Julius J.; Behrendt, Patrick; Wedemeyer, Heiner; Cornberg, Markus; Maasoumy, Benjamin
Summary: Background: Acute kidney injury (AKI) is a frequent complication in patients with decompensated cirrhosis. Studies reported conflicting results regarding the nephrotoxic potential of iodinated contrast medium (CM) for computer tomography (CT). Aim: To investigate the impact of diagnostic CM application on kidney function in patients with decompensated cirrhosis. Methods: First, we evaluated the impact of diagnostic CM‐CT on AKI incidence in a cross‐sectional approach. Second, we analysed 28‐day AKI incidence post‐CM‐CT in patients with impaired kidney function ( i.e ., creatinine >133 μmoL/L). Third, we excluded all patients with relevant interventions besides CM‐CT. All remaining patients were matched via propensity score matching (PPSM) and further analysed. Last, we validated the results in an independent dataset of prospectively collected registry data of 118 patients with decompensated cirrhosis. Here, plasma samples were analysed regarding neutrophil‐gelatinase‐associated‐lipocalin (NGAL). Results: Of the 611 included patients, 98 (16%) received CM‐CT. CM‐CT was not associated with AKI in the cross‐sectional approach (CM‐CT:8% vs. no CM‐CT:15%; p = 0.08). Furthermore, CM‐CT was not associated with higher 28‐day AKI incidence among patients with impaired kidney function (HR:0.79; 95% CI 0.45–1.38; p = 0.40). The PPSM cohort revealed no association between CM‐CT and AKI or severe AKI (HR:1.28, p = 0.45 and HR:1.62; p = 0.43). Moreover, CM‐CT did not result in worsening of kidney function after CM application. In the validation cohort, CM‐CT was also not linked to AKI ( p = 0.85) and NGAL levels were not increased in those with CM‐CT (CM‐CT:309 ng/ml vs. No CM‐CT:266 ng/ml, p = 0.35). Conclusion: Decompensated cirrhosis per se should not preclude diagnostic CM‐CT. Abstract : Impact of CT‐contrast medium for diagnostic purposes on kidney failure in decompensated cirrhosis.